Active agents of change: A conceptual framework for social justice-orientated citizenship education. Issue 2 (11th August 2022) - Egan-Simon, Daryn
Social justice–orientated citizenship education (SJCE) can help young people to develop the knowledge, skills and dispositions to work collectively towards solutions to problems such as human rights violations, global poverty and environmental sustainability (DeJaeghere and Tudball, 2007; Banks, 2017; Hartung, 2017). Furthermore, SJCE can enable young people to think critically, consciously and compassionately and allow them to grow intellectually with a concern for equality and justice. This paper presents a conceptual framework for SJCE for educators and educational researchers wishing to explore citizenship education within social justice contexts. The framework is based on four constitutive elements: agency, dialogue, criticality and emancipatory knowledge, and has its philosophical foundations deeply rooted in the values and principles of critical pedagogy (Kincheloe, 2004; McLaren, 2014; Giroux, 2016). This conceptual framework for SJCE is ultimately concerned with developing justice-orientated active agents of change who are concerned with making the world more democratic, equitable and just.